2012
DOI: 10.1002/ajmg.b.32070
|View full text |Cite
|
Sign up to set email alerts
|

Defining genetically meaningful language and personality traits in relatives of individuals with fragile X syndrome and relatives of individuals with autism

Abstract: BACKGROUND Substantial phenotypic overlap exists between fragile X syndrome (FXS) and autism, suggesting that FMR1 (the gene causing FXS) poses a significant risk for autism. Cross-population comparisons of FXS and autism therefore offer a potentially valuable method for refining the range of phenotypes associated with variation in FMR1. This study adopted a broader phenotype approach, focusing on parents who are at increased genetic liability for autism or FXS. Women who were carriers of FMR1 in its premutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 67 publications
10
100
0
Order By: Relevance
“…Furthermore, premutation carriers of FMR1 show subclinical pragmatic features that are similar in quality and severity with those seen in the broad autism phenotype, which supports a role of FMR1 in a broad range of pragmatic language features associated with ASD (Losh, Klusek, et al, 2012). Thus, the delineation of pragmatic language features that may overlap or diverge in ASD and FXS is a promising method for identifying phenotypic commonalities that may stem from biological disruptions associated with FMR1 .…”
Section: Pragmatic Language In Autism Spectrum Disorder and Fragile Xsupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, premutation carriers of FMR1 show subclinical pragmatic features that are similar in quality and severity with those seen in the broad autism phenotype, which supports a role of FMR1 in a broad range of pragmatic language features associated with ASD (Losh, Klusek, et al, 2012). Thus, the delineation of pragmatic language features that may overlap or diverge in ASD and FXS is a promising method for identifying phenotypic commonalities that may stem from biological disruptions associated with FMR1 .…”
Section: Pragmatic Language In Autism Spectrum Disorder and Fragile Xsupporting
confidence: 56%
“…The groups were similar in race, household income, and maternal education level ( ps > .112); see Table 2. The standardized pragmatic language data for forty-two children (5 with ASD-O, 9 with FXS-ASD, 3 with FXS-O, 7 with DS, 18 with TD) have been previously analyzed by Losh et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Wilson and associates (2013) proposed that phonological processing differences in the brain appear to be a basic feature of the BAP. However, similar to Losh et al (2012), Wilson et al (2013) indicated that replication of their findings are necessary before any firm conclusions can be drawn.…”
Section: Phonological Processingmentioning
confidence: 72%
“…Individual carriers of the fragile X premutation (CGG repeats between 55 and 200) are at high risk for developing a neurodegenerative disorder called Fragile X-associated tremor/ataxia syndrome (FXTAS) (Garcia-Arocena and Hagerman, 2010). Additionally, carriers can develop neuropathy, fertility problems, executive function deficits, attention deficits, memory problems, language dysfluencies, affective disorders, anxiety, attention deficit/hyperactivity disorder (ADHD) and sleep problems (Sullivan et al, 2011; Seltzer et al, 2012; Losh et al, 2012; Hagerman and Hagerman, 2013). Approximately 20% of the female carriers develop fragile-X-associated primary ovarian insufficiency (FXPOI) (Sullivan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%